Spatial and Temporal Distribution of Dopaminergic Neurons during Development in Zebrafish - Du, Yuchen; Guo, Qiang; Shan, Minghui; Wu, Yongmei; Huang, Sizhou; Zhao, Haixia; Hong, Huarong; Yang, Ming; Yang, Xi; Ren, Liyi; Peng, Jiali; Sun, Jing; et al. (Frontiers in Neuroanatomy, 2016)
As one of the model organisms of Parkinson’s disease (PD) research, the zebrafish has its advantages, such as the 87% homology with human genome and transparent embryos which make it possible to observe the development of dopaminergic neurons in real time. However, there is no midbrain dopaminergic system in zebrafish when compared with mammals, and the location and projection of the dopaminergic neurons are seldom reported. In this study, Vmat2:GFP transgenic zebrafish was used to observe the development and distribution of dopaminergic neurons in real time. We found that diencephalons (DC) 2 and DC4 neuronal populations were detected at 24 h post fertilization (hpf). All DC neuronal populations as well as those in locus coeruleus (LC), raphe nuclei (Ra) and telencephalon were detected at 48 hpf. Axons were detected at 72 hpf. At 96 hpf, all the neuronal populations were detected. For the first time we reported axons from the posterior tubercle (PT) of ventral DC projected to subpallium in vivo. However, when compared with results from whole mount tyrosine hydroxylase (TH) immunofluorescence staining in wild type (WT) zebrafish, we found that DC2 and DC4 neuronal populations were mainly dopaminergic, while DC1, DC3, DC5 and DC6 might not. Neurons in pretectum (Pr) and telencephalon were mainly dopaminergic, while neurons in LC and Ra might be noradrenergic. Our study makes some corrections and modifications on the development, localization and distribution of zebrafish dopaminergic neurons, and provides some experimental evidences for the construction of the zebrafish PD model.